Karakteristik Mikrobiologis Dan Fisik Yogurt Susu Kambing Dengan Penambahan Probiotik Lactobacillus Acidophilus - Zain, Wieda N H; Kuntoro, Bambang (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2017)
Introductions of fermented milk production in the Pekanbaru city is still very limited. One of the raw materials for the manufacture of fermented milk is goat's milk and have started to be developed in the Pekanbaru city. Diversification efforts of dairy productsis expected to introduce a fermented milk as a functional food with the addition of probiotic bacteria. Microbiological and physical quality becomes an important parameter in this study to determine the quality of goat milk yogurt produced to fit the standardized yogurt products. The design of experiment used in this experiment was a Completely Randomized Design with three replications for each treatment. Parameters observed were lactic acid bacteria population, total plate count, pH and titratable acidity. The results showed of yogurt starter culture population (S. thermophilus and L. bulgaricus) and probiotic bacteria L. acidophilusin the range of 9 log 10 CFU/mL, with the average of pH value was 4 and the titratable acidity was 1.743%. Keywords :microbiological, physical, Lactobacillus acidophilus, goat milk, yoghurt